What counts as love - Crotty, Marian, 1980- (John Simmons short fiction award., 2017)
"In these nine stories, Marian Crotty inhabits the lives of people searching for human connection. Her characters, most often young women, are honest, troubled, and filled with longing. In the title story, a young woman begins a job on a construction site after leaving an abusive marriage. In "Crazy for You," two girls spy on a neighbor's sex life, while their own sexuality hovers in the distance. In "A Real Marriage," a college student marries a boyfriend to help him stay in the United States. In "The Fourth Fattest Girl at Cutting Horse Ranch," the daily life of a residential treatment center for eating disorders is disrupted by the arrival of a celebrity. The stories are set in Arizona, North Carolina, Pennsylvania, Maryland, and the Persian Gulf, and often touch on themes of addiction, class, sexuality, and gender. What Counts as Love is a poignant, often funny collection that asks us to take it and its characters seriously"--